Structure-aided design of novel inhibitors of HIV protease based on a benzodiazepine scaffold - Schimer, Jiří; Oberwinkler, Heike; Kräusslich, Hans-Georg (Journal of medicinal chemistry, 2012)
HIV protease is a primary target for the design of virostatics. Screening of libraries of non-peptide low molecular weight compounds led to the identification of several new compounds that inhibit HIV PR in the low micromolar range. X-ray structure of the complex of one of them, a dibenzo[b,e][1,4]diazepinone derivative, showed that two molecules of the inhibitor bind to the PR active site. Covalent linkage of two molecules of such a compound by a two-carbon linker led to a decrease of the inhibition constant of the resulting compound by 3 orders of magnitude. Molecular modeling shows that these dimeric inhibitors form two crucial hydrogen bonds to the catalytic aspartates that are responsible for their improved activity compared to the monomeric parental building blocks. Dibenzo[b,e][1,4]diazepinone analogues might represent a potential new class of HIV PIs.
Gesehen am 07.05.2018